Pelaksanaan Perjanjian Bagi Hasil Kemitraan Tanaman Jagung Antara Pt. Sumbawa Bangkit Sejahtera Dengan Petani Penggarap Di Kabupaten Sumbawa - Maghfirrah, Schintya; Andriyani, Shinta (Private Law, 2024)
The purpose of the study is to provide recommendations and solutions to improve the implementation of corn crop partnership profit-sharing agreements and the distribution of corn crop yields in the type of sharing portions between companies and sharecroppers in Sumbawa Regency. This may involve suggestions for improvements in aspects of agreements, management, training, or other policies that support the sustainability of the partnership program. The research method in this research uses normative-empirical legal research methods. The conclusion of the study showed that for resolving the legal issues that Law Number 2 of 1960 concerning Production Sharing Agreements, the implementation of a corn plant partnership profit-sharing agreement if the land owner or owner’s capital and sharecroppers are each willing, where the sharecroppers are willing to carry out crop planting, and managing a certain type of plant and the land owner is also willing to provide the finance for the crop plantation, then this agreement can be agreed between the parties.